WAYANG PURWA DALAM SENI LUKIS DEKORATIF - DWI YUNIZAL, Drs. Erfahmi, M.Sn, Drs. Mediagus (Serupa The Journal of Art Education, 2014)
This works which with wayang kulit Purwa objects in decorative paintings, is aim to visualize the local culture by presenting a new case based on the socio-cultural while deepening the concepts and maturing engineering capabilities.  The  sources  of  ideas  is  based  on  the  various  cases  which  is weakening of the rate in younger generation in appreciate the puppet, the audience of the puppets which has been generally the older generation over the age of 50 years. In this cases the authors worked with a puppet trying to show a different side of the decorative style of painting. Form the process of long creation, it can be concluded that nobility inherent value of ten works is the value of patience, courtesy, trust in Allah, the effort to achieve the wishes, devotion to parents, get knowledge, wisdom, justice in attitude, honesty, courage and so forth.Keywords : Wayang Purwa, Seni Lukis Dekoratif.